Do the acute lymphoblastic leukemia and non-hodgkin lymphoma patients have a worse prognosis of COVID-19 infection in children?: a case report - Nadirah Rasyid Ridha; Bahrul Fikri; Rahmawaty Rahimi; Amiruddin Laompo; Conny Tanjung; Dasril Daud; Nasrum Massi (Health Science Journal of Indonesia, 2021)
Background: Coronavirus Disease 2019 (COVID-19) is a contagious disease caused by a new type of Coronavirus namely Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Children with tumors or autoimmune diseases are more susceptible, because of suppression of their immune system, chemotherapy, radiotherapy, or surgery on tumors. Case presentation: We present the clinical features 3 Acute Lymphoblastic leukemia and 1 Non-Hodgkin lymphoma patients who were infected with COVID-19 since July to August 2020 in our hospital. These were the first four cases identified as COVID-19 positive in Dr Wahidin Sudirohusodo Hospital. Case 1, 2, and 4 were diagnosed as moderate and common type of COVID-19, while case 3 was classified as severe type. They may be transmitted COVID-19 infection during hospitalization. All cases were recovered from COVID-19 after a combination therapy against virus, bacteria, and also respiratory support. Conclusion: Our case series of four pediatric cancer patients showed a good outcome after prompt treatment, suggesting that malignancy in children may not be a contributor factor for COVID-19 recovery. Keywords: COVID-19; acute lymphoblastic leukemia; non-hodgkin lymphoma; children Abstrak Latar belakang: Covid-19 (Coronavirus disease 2019) adalah penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Anak yang menderita kanker atau penyakit autoimun lebih rentan tertular karena penurunan system kekebalan tubuh, dampak kemoterapi, radioterapi, atau operasi tumor. Penyajian kasus: Kami melaporkan 3 pasien leukemia limfoblastik akut dan 1 pasien limfoma non-Hodgkin yang terinfeksi Covid-19 sejak Juli-Agustus 2020. Kasus tersebut adalah 4 kasus pertama yang teridentifikasi Covid-19 di Rumah Sakit Dr. Wahidin Sudirohusodo. Kasus 1,2, dan 4 terdiagnosis positif Covid -19 derajat sedang, sedangkan kasus 3 tergolong berat. Mereka kemungkinan terinfeksi Covid-19 saat perawatan. Semua kasus dinyatakan sembuh dari Covid-19 setelah pemberian obat anti virus, antibiotik, dan alat bantu pernapasan. Kesimpulan: Serial kasus dari 4 pasien kanker anak dengan outcome yang baik setelah pengobatan yang cepat mengindikasikan bahwa penyakit keganasan pada anak kemungkinan bukan faktor yang berkontribusi dalam kesembuhan Covid-19. Kata kunci: COVID-19; leukemia limfoblastik akut; limfoma non-hodgkin; anak